(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Every disease in Ayurveda, the science of life has a different view in understanding a disease in a systematic way. Among the Astangas of Ayurveda, Shalakya tantra is given importance equally by all Acharyas. Acharya Sushruta has explained seventysix eye diseases with their medical and surgical management in detail. Puyalasa, one of the Sandhigataroga can be correlated to dacryocystitis based on the symptomatology which includes swelling in Kaninika sandhi, which later on undergoes suppuration causing thick purulent discharge. Dacryocystitis is the inflammation of the lacrimal sac is not an uncommon condition, which is an important cause of ocular morbidity, both in children and adults. The management constitutes of simple topical medication to surgery and with certain amount of recurrences. Though Puyalasa is due to Tridosha it is considered as a curable disease and the treatment includes Siravyadha, Upanaha and Anjana kriya and internal medication which can reduce the recurrence rate and other secondary diseases in eyes. The clinical features and the treatment of Dacryocystitis has similarities with the disease Puyalasa which has been told by our ancient seers. The drugs mentioned in the treatment of the disease Puyalasa are mainly having Doshahara guna, Vrana shodhaka guna and are Chakshushya. Based on the Yukti of the physician the selection of the appropriate treatment depends and based on this the recurrence rate of the disease can be controlled well.